Intravitreal Application: Physicochemical Properties of Drugs Dissolved in Silicone Oils of Different Density in Comparison to the Porcine Vitreous Body - Maximilian Hammer; Sonja K. Schickhardt; Patrick R. Merz; Ramin Khoramnia; Alexander F. Scheuerle; Walter Mier; Philipp Uhl; Gerd U. Auffarth (Pharmaceutics, 2022)
Silicone oil endotamponades provide a reservoir for drugs in the eye. Following vitrectomy surgery to treat retinal detachments, extensive diabetic retinopathy or endophthalmitis, they can be used as long-term lipophilic depots. This study aimed to investigate the physicochemical properties of intravitreally applied drugs of different lipophilicity, namely vancomycin, ceftazidime and voriconazole. For this purpose, an in vitro model of the silicone-oil-filled eye compared to porcine vitreous bodies (PVBs) was used. In a glass container, either light or heavy silicone oil or PVB was set into equilibrium with an aqueous fluid. Vancomycin, voriconazole and ceftazidime were added in concentrations commonly applied in clinical practice. The time course of the concentration of the drugs was determined in the hydrophilic phase for up to 24 h. With silicone oil present, the concentrations of vancomycin, voriconazole and ceftazidime were elevated in the aqueous humor when compared to the vitreous body (p < 0.001 for all drugs). With increasing lipophilicity, higher concentrations of the drug dissolved in silicone oil after 24 h (52.7%, 49.1% and 34.3% for vancomycin, ceftazidime and voriconazole, respectively). While no difference between lighter- and heavier-than-water silicone oil was apparent for vancomycin and ceftazidime (p = 0.17 and p = 0.72), voriconazole dissolved significantly better in the heavier-than-water silicone oil (p = 0.002). A higher-than-expected percentage of the glycopeptide vancomycin dissolved in the porcine vitreous body, possibly due to protein binding. In conclusion, silicone oils influence the drug concentration and distribution of intravitreally applied drugs depending on their lipophilicity. The addition of F6H8 used to create heavy silicone oils attenuates these effects for lipophilic drugs. Knowledge of the distribution of these intravitreally applied drugs is crucial to ensure the desired anti-infectious effect.